Red-emissive carbon dot-cobalt oxyhydroxide nanosystem: A turn-on sensor for α-Glucosidase activity and inhibitor identification - Huihui Sun; Chuanyuan Gao; Yumin Yang; Changqing Liu; Han Qin; Mengyuan Tan; Jin Li; Xiaoxia Li; Kunze Du; Yanxu Chang (Materials Today Bio)
The development of efficient methods for sensing αlpha-glucosidase (α-Glu) and screening its inhibitors has attracted significant attention due to their pivotal role in discovering therapeutic medicines for Type 2 diabetes. Herein, a low-cost and sensitive fluorometric strategy based on red carbon dots (R-CDs) and cobalt oxyhydroxide nanosheets (CoOOH NSs) had been established to detect α-Glu and screen its inhibitory compounds in natural products. As a switched fluorescence source, the fluorescence of R-CDs at 625 nm could be quenched by CoOOH NSs via Förster resonance energy transfer (FRET), assembled into nonfluorescent R-CDs@CoOOH nanocompositecomposites (R-CDs@CoOOH NCs). α-Glu hydrolyzed L-ascorbic acid-2-O-α-D-glucopyranose to produce ascorbic acid, which could reduce CoOOH NSs to Co2+, destroying R-CDs@CoOOH NCs and restoring the emission of red fluorescence. The proposed method exhibited a linear α-Glu range from 0.01 to 15 U mL−1 and a low limit of detection (LOD) of 0.0037 U mL−1. Meanwhile, high-performance liquid chromatography-DAD-fraction collector (HPLC-DAD-FC) had been employed and combined with ultra-high-performance liquid chromatography-triple quadrupole time-of-flight mass spectrometry to isolate, enrich, and characterize compounds from Polygonum cuspidatum (PC). This strategy was further extended by integrating the fluorometric platform with the HPLC-DAD-FC system to explore the inhibitory effects of PC extracts and anti-diabetic ingredients. Finally, 85 constituents were identified, with seven compounds exhibiting high α-Glu inhibitory activity. Consequently, the established strategy could accurately determine α-Glu in vitro and screen its inhibitors from natural products.